Did the Arab Spring Reduce MENA Countries' Growth? - Mahmoud Arayssi; Ali Fakih; Nathir Haimoun (Institute of Labor Economics (IZA), 2019)
This paper examines the economic ramifications of the recent political reconfigurations that the MENA region witnessed, commonly known as the Arab Spring, utilizing MENA countries data during period 2005-2016. Using the Arellano-Bond dynamic panel estimation, the paper estimates a growth model using the difference in the log of GDPC between periods t and t+1. Buttressed by sufficient empirical evidence, the paper's findings corroborate that the Arab Spring had been negatively associated with growth.
Keywords: G2; O16; P48; N25; 330; Arab Spring; growth; MENA countries; panel data